ANALYSIS OF GRDP DETERMINANTS ANALYSIS OF THE TOURISM SECTOR IN 10 SUMATRA PROVINCE 2010-2018 - Muhammad Farras Nasrida (Quantitative Economics Journal, 2021)
The main purpose of this study is to analyze the determinants of PDRB tourism sector in 10 provinces of Sumatra in 2010-2018. There are 4 main variable factors (gross regional domestic product, tourists, accommodation, room occupancy). The study tried to identify factors that influenced the determinants of the tourism sector in 10 provinces in Sumatra from 2010 to 2018. The type of data used in this study is secondary data with a total of 90 data panels which is a combination of spatial data and time series that are quantitative data. Data sources obtained from the Central Statistics Agency (BPS) in 10 Provinces, as well as other sources related to this research, are delivered through print media, electronic media, and websites. The technique is used in the collection of this data by recording directly, copying, and downloading from the source of the website in question. The results of the analysis that has been conducted on the Determinant Analysis of PDRB Tourism Sector in Sumatra Island then obtained the following conclusions: The number of tourists, accommodation, room occupancy has a positive and significant effect on the PDRB tourism sectorKeywords: PDRB tourism sector, Number of Tourists, Accommodation, Room Occupancy